Surgical Mask Partition Reduces the Risk of Noncontact Transmission in a Golden Syrian Hamster Model for Coronavirus Disease 2019 (COVID-19). (30th May 2020) - Chan, Jasper Fuk-Woo; Yuan, Shuofeng; Zhang, Anna Jinxia; Poon, Vincent Kwok-Man; Chan, Chris Chung-Sing; Lee, Andrew Chak-Yiu; Fan, Zhimeng; Li, Can; Liang, Ronghui; Cao, Jianli; Tang, Kaiming; Luo, Cuiting; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is believed to be mostly transmitted by medium- to large-sized respiratory droplets, although airborne transmission may be possible in healthcare settings involving aerosol-generating procedures. Exposure to respiratory droplets can theoretically be reduced by surgical mask usage. However, there is a lack of experimental evidence supporting surgical mask usage for prevention of COVID-19. Methods: We used a well-established golden Syrian hamster SARS-CoV-2 model. We placed SARS-CoV-2-challenged index hamsters and naive hamsters into closed system units each comprising 2 different cages separated by a polyvinyl chloride air porous partition with unidirectional airflow within the isolator. The effect of a surgical mask partition placed between the cages was investigated. Besides clinical scoring, hamster specimens were tested for viral load, histopathology, and viral nucleocapsid antigen expression. Results: Noncontact transmission was found in 66.7% (10/15) of exposed naive hamsters. Surgical mask partition for challenged index or naive hamsters significantly reduced transmission to 25% (6/24, P = .018). Surgical mask partition for challenged index hamsters significantly reduced transmission to only 16.7% (2/12, P = .019) of exposed naive hamsters. Unlike the severe manifestations of challenged hamsters, infected naive hamsters had lower clinical scores, milder histopathological changes, and lower viral nucleocapsid antigen expression in respiratory tract tissues. Conclusions: SARS-CoV-2 could be transmitted by respiratory droplets or airborne droplet nuclei which could be reduced by surgical mask partition in the hamster model. This is the first in vivo experimental evidence to support the possible benefit of surgical mask in prevention of COVID-19 transmission, especially when masks were worn by infected individuals. Abstract : Noncontact transmission of SARS-CoV-2 was demonstrated in a Syrian hamster model. Surgical mask partition significantly reduced the transmission of SARS-CoV-2 from challenged index hamsters to the exposed naive hamsters via respiratory droplets and/or airborne droplet nuclei.